Investigating occupational burnout among the operation room personnel of Shahid Mohammadi hospital in Bandar Abbas in 2015 - Hosna Shadman; Zahra Atazadegan; Hossein Sharafi (Disease and Diagnosis, 2017)
Introduction and aims: Occupational burnout is a syndrome including emotional exhaustion, depersonalization, self-efficacy and involvement. Medical staff are susceptible to occupational burnout due to physical, mental and emotional stress. The present research aims to investigate the operation room staff’s burnout in Shahid Mohammadi hospital of Bandar Abbas. Methods: In this descriptive/analytical research, the sample size was 150 subjects working in the operation room of Shahid Mohammadi hospital in Bandar Abbas. They were selected through a convenience. They then received the data gathering instrument which was a questionnaire of demographic information and Maslach burnout inventory. In Maslach inventory, the rating of each dimension of burnout is measured including: emotional exhaustion (score range 0-54), depersonalization (0-30), self-efficacy (0-48) and obsession (0-18). The inventory is rated in a likert-scale. The data were finally analyzed using SPSS-17. Results: The mean scores found were as the following: 14.49 for emotional exhaustion (low), 5.75 for depersonalization (low), 32.61 for selfefficacy (moderate) and 4.35 for obsession (low). There was a statistically significant correlation in terms of emotional exhaustion between age(P=0.032) and sex(0.017) variables and between obsession and marital status(P=0.003). Emotional exhaustion was found to be higher among men than women, and was found to be higher in the 20-30 age group than others. Moreover, the married were found to be more obsessed than the single. Conclusions: A low level of occupational burnout was found in the present research as compared to others. Therefore, authorities should make attempts to prevent occupational burnout.